The tL structure within the leader region of Escherichia coli ribosomal RNA operons has post-transcriptional functions. - Theissen, G (1990)
We have investigated a series of mutations within a plasmid encoded E. coli ribosomal RNA leader region. The mutations are localized within a structure known as tL, which has been shown to mediate RNA polymerase pausing in vitro, and which is assumed to have a control function in rRNA transcription antitermination. The effects of the mutated plasmids were analyzed by in vivo and in vitro experiments. Some of the base change mutations led to severely reduced cell growth. As opposed to previous results obtained with mutants where the tL structure has been deleted in part or totally, the tL base change mutations did not result in polar transcription in vivo, rather they revealed a general reduction in the amount of the promoter proximal 16S versus the distal 23S RNA. The deficiency of the 16S RNA, which was most pronounced for some of the slowly growing transformants, can only be explained by a post-transcriptional degradation. In addition, many mutants showed a defective processing after the initial RNase III cut. In line with these results a quantitative analysis of the ratio of ribosomal subunits and 70S tight couple ribosomes showed a reduced capacity to form stable 70S particles for the slowly growing mutants. Together, these findings indicate an important function of the tL structure in post-transcriptional events like processing of rRNA precursors and correct assembly of 30S subunits.